2017
DOI: 10.3389/fmolb.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasomal ATPases Use a Slow but Highly Processive Strategy to Unfold Proteins

Abstract: All domains of life have ATP-dependent compartmentalized proteases that sequester their peptidase sites on their interior. ATPase complexes will often associate with these compartmentalized proteases in order to unfold and inject substrates into the protease for degradation. Significant effort has been put into understanding how ATP hydrolysis is used to apply force to proteins and cause them to unfold. The unfolding kinetics of the bacterial ATPase, ClpX, have been shown to resemble a fast motor that traps un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…This study uncovered several surprising properties of the structure and function of the PAN proteasomal ATPase: (1) PAN’s CCs are not conformationally symmetric, (2) global conformation of the CCs does not appear to cycle around the ring, and (3) local changes in two of the CC conformations (C2 and C3) can regulate PAN’s activity. Previous biochemical studies suggest that PAN adopts asymmetrical conformations 48 , 50 , 51 , but the present study provides direct structural evidence of this, at least for the CC domains. This finding is critical, because up until this point it has been assumed based on crystal structures of PAN’s N-terminus that it is symmetric.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…This study uncovered several surprising properties of the structure and function of the PAN proteasomal ATPase: (1) PAN’s CCs are not conformationally symmetric, (2) global conformation of the CCs does not appear to cycle around the ring, and (3) local changes in two of the CC conformations (C2 and C3) can regulate PAN’s activity. Previous biochemical studies suggest that PAN adopts asymmetrical conformations 48 , 50 , 51 , but the present study provides direct structural evidence of this, at least for the CC domains. This finding is critical, because up until this point it has been assumed based on crystal structures of PAN’s N-terminus that it is symmetric.…”
Section: Discussioncontrasting
confidence: 41%
“…Since crosslinking C1 has no effect on activity, and since crosslinking C1+C3 lowers PAN’s activity, these data indicate that stabilizing C3 by crosslinking stabilizes a functional but low activity state of PAN. This suggests that crosslinking the C3 state results in the slowing of some step in the ATP hydrolysis cycle (ATP binding, ATP hydrolysis/phosphate leaving, or ADP off rate) but does not have an effect on the mechanochemical coupling of ATP hydrolysis to substrate unfolding previously observed for proteasomal ATPases 50 . While PAN 87+73C alone in the reduced state had a slightly lower Vmax (42 ± 1 ATP/PAN/min), it had a similar Km as WT-PAN (556 ± 29 mM) (Supplementary Table 1 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Martin and colleagues recently used single-molecule analysis to analyze the unfolding of a GFP-fusion protein by ClpXP and showed that unfolding depends of the power generated by the pore loops and thus requires frequent and forceful pulling on the substrate (Rodriguez-Aliaga et al, 2016). However, Smith an coworkers showed that translocation by the 26S or PAN is more processive than by ClpXP and depends predominantly on the force generated by the pore loops rather than the frequency with which these loops pull on the substrate (Snoberger et al, 2017). …”
Section: Translocation Of the Polypeptide Through The Atpase Ringmentioning
confidence: 99%
“…Processive enzymes play the important roles in various biological activities such as DNA/RNA synthesis (13,14), cargo transport (15,16), and protein (17,18) and polysaccharide (19 -21) degradations. Once processive enzymes bind to their substrates, they can repeat multiple cycles of catalysis without dissociation (22,23).…”
mentioning
confidence: 99%